2022
DOI: 10.3389/fcimb.2022.864626
|View full text |Cite
|
Sign up to set email alerts
|

A Search for Novel Legionella pneumophila Effector Proteins Reveals a Strain Specific Nucleotropic Effector

Abstract: Legionella pneumophila is an accidental human pathogen that causes the potentially fatal Legionnaires’ disease, a severe type of pneumonia. The main virulence mechanism of L. pneumophila is a Type 4B Secretion System (T4SS) named Icm/Dot that transports effector proteins into the host cell cytosol. The concerted action of effectors on several host cell processes leads to the formation of an intracellular Legionella-containing vacuole that is replication competent and avoids phagolysosomal degradation. To date … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…The outbreak was associated with the novel sequence type (ST) 1905 of L. pneumophila subspecies fraseri serogroup 1 strain (PtVFX/2014), which probably originated from a local industrial cooling tower ( 6 , 7 ). In-depth genomic analyses showed that PtVFX/2014 possesses a unique and mosaic genomic backbone marked by specific evolutionary and genetic traits ( 3 ), including a recently identified novel effector with nucleotropism ( 8 ), that may affect its ability to adapt and persist in diverse environments and cause human disease. The L. pneumophila ST1905 strain was also implicated by the strongest evidence to date of person-to-person transmission of LD ( 3 , 4 ).…”
mentioning
confidence: 99%
“…The outbreak was associated with the novel sequence type (ST) 1905 of L. pneumophila subspecies fraseri serogroup 1 strain (PtVFX/2014), which probably originated from a local industrial cooling tower ( 6 , 7 ). In-depth genomic analyses showed that PtVFX/2014 possesses a unique and mosaic genomic backbone marked by specific evolutionary and genetic traits ( 3 ), including a recently identified novel effector with nucleotropism ( 8 ), that may affect its ability to adapt and persist in diverse environments and cause human disease. The L. pneumophila ST1905 strain was also implicated by the strongest evidence to date of person-to-person transmission of LD ( 3 , 4 ).…”
mentioning
confidence: 99%